1991
DOI: 10.1007/bf00154876
|View full text |Cite
|
Sign up to set email alerts
|

The subretinal fluid in retinal detachment

Abstract: Following retinal detachment, subretinal fluid (SRF) fills the neoformed space. Subsequently subretinal and preretinal strands of proliferative tissue begin to form. We have collected the subretinal fluid withdrawn during retinal detachment surgery. We have studied subretinal fluid cytologically to evaluate the number and the type of cells present in the fluid, and by means of transmission electron microscopy. The first cell type to be present in the fluid represented degenerated aspects of pigmented epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…This is consistent with Veckeneer's view that the inferior RD is more prone to postoperative PSF, and that the duration is longer [15,20,21]. Prolonged retentions of vitreous diffusion into the subretinal fluid may lead to the remodification of protein components and macromolecules [22,23], resulting in decreased absorption of SRF by RPE. When the retina is detached for a significant Fig.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with Veckeneer's view that the inferior RD is more prone to postoperative PSF, and that the duration is longer [15,20,21]. Prolonged retentions of vitreous diffusion into the subretinal fluid may lead to the remodification of protein components and macromolecules [22,23], resulting in decreased absorption of SRF by RPE. When the retina is detached for a significant Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Macrophages are not normally found in significant numbers in healthy retina. When the retina however becomes separated from the RPE as in retinal detachment, clumps of macrophages can be seen in the subretinal space 22 and on the surface of the RPE. These may be derived either from RPE cells or recruited from the choroid.…”
Section: Discussionmentioning
confidence: 99%
“…3) (Heidelberg Spectralis, Heidelberg Engineering, Germany). Biochemical and histological analyses have furthermore shown that large molecules such as proteins and GAG, as well as cells and cellular debris, are concentrated in longstanding SRF [35,36]. These compounds cannot be removed through ion or water channels, resulting in an imbalance between the decreased capability of and the increased need for phagocytosis by RPE cells.…”
Section: Rpe Malfunction?mentioning
confidence: 96%